MITIGATING EARNINGS MANAGEMENT THROUGH FAITH: THE MODERATING ROLE OF RELIGIOSITY ON BLOCKHOLDER INFLUENCE IN INDONESIA (International Conference on Economics, Business, and Management Research (ICEBMR), 2025)
This study investigates the impact of controlling shareholders on earnings management in Indonesian firms and examines whether religiosity moderates this relationship. Using 2,238 firm-year observations of companies listed on the Indonesia Stock Exchange (2017–2021), multiple linear regression and multi-group regression analyses are applied. The final sample consists of 80 consumer goods firms (30 non-cyclical and 50 cyclical), yielding 320 firm-year data. Results indicate that controlling shareholders significantly increase earnings management, supporting the entrenchment theory. However, religiosity does not significantly moderate this relationship, suggesting that its influence as an informal governance mechanism remains limited in the Indonesian context. Additional findings reveal that leverage tends to strengthen earnings management practices. This research contributes to corporate governance literature by being among the first to empirically test religiosity as a moderating factor in the ownership–earnings management nexus. Practically, the study highlights the potential role of embedding religious values into corporate culture to curb unethical reporting behavior, although the measurement of religiosity via BEI proxy is a limitation. Future studies should broaden sectoral coverage and apply more direct measures of religiosity.
Keywords: Controlling Shareholders; Religiosity; Earnings Management; Agency Theory; Indonesia